Zur Wechselbeziehung von Schreiben und Reflektieren: Eine Untersuchung der Verfasserreferenz in schriftlichen Reflexionen des Deutschunterrichts von Lehramtsstudierenden - Behrendt, Renata (HERMES - Journal of Language and Communication in Business, 2025)
On the interrelationship between writing and reflection. An investigation of author reference in written reflections on German lessons by teacher training students. The article explores the interrelationship between writing and reflection based on written reflections composed by student teachers of German during their teacher training. In teacher education, reflection is regarded as a key competence for professionalization. Writing serves as a means to foster reflective competence. The production of written reflections within academic teaching and learning contexts entails the demands of both academic writing and reflective thinking. Therefore, the reflections are analysed through the lenses of writing research and reflection theory. At the heart of the analysis lies Steinhoff’s concept of authorial reference, which focuses on the use of the pronouns “ich” “wir,” and “man,” enabling the identification of roles through which writers position themselves within their texts – such as the “Verfasser-ich,” “Gemeinschafts-Wir,” or “Autoren-Man.” What the writers reflect on, and how they do so within these assumed roles, is analyzed using the models developed by Hilzensauer and Bräuer. The findings suggest that the deliberate use of the personal pronoun “I” can contribute to the development of reflective competence. From a didactic perspective, it appears beneficial to encourage students to engage with (their own) written reflections in order to individually support processes of professionalization during teacher education.